1995
DOI: 10.1177/101053959500800201
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Pattern of Body Mass Index (BMI) and Prevalence of Obesity in a Saudi Population

Abstract: The present study was conducted to assess the pattern of body mass index (BMI) prevalence of obesity, and the association between obesity and other health-related problems in a Saudi population. The study was conducted in Queza district of Jeddah, Saudi Arabia. A systematic random sample of Saudi nationals aged 16 years and above were selected (total number 1037; 611 males and 426 females). The study population was clinically examined and a specially-designed questionnaire was administered to obtain the inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
(1 reference statement)
6
10
0
Order By: Relevance
“…Obesity in adult Saudi females has been reported in other studies (Binhemed, 1991, Kordy and El-gamal, 1995, Al-Nuaim et al, 1996and El-Hazmi, 1997. A recent national study by Al-Nuaim et al (1996) showed that 27% of adult females in Saudi Arabia were overweight and 24% were obese, based on BMI criteria.…”
Section: Discussionmentioning
confidence: 68%
“…Obesity in adult Saudi females has been reported in other studies (Binhemed, 1991, Kordy and El-gamal, 1995, Al-Nuaim et al, 1996and El-Hazmi, 1997. A recent national study by Al-Nuaim et al (1996) showed that 27% of adult females in Saudi Arabia were overweight and 24% were obese, based on BMI criteria.…”
Section: Discussionmentioning
confidence: 68%
“…First, the results of the 84 eligible correlate studies are described, followed by the data on the seven intervention studies …”
Section: Resultsmentioning
confidence: 99%
“…All correlate studies were cross‐sectional, except for one longitudinal study . Half of the studies were performed in Saudi Arabia, and a large number were performed in Kuwait . Approximately 30% of studies involved university students.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity is prevalent in Saudi Arabian adolescents and represents an emerging epidemic and important public health problem [4][5][6][7][8][9][10]. The overall prevalence of overweight (=BMI of [25][26][27][28][29][30] and obesity (=BMI>30) subjects are 13.8% and 20.5%, respectively.…”
mentioning
confidence: 99%